2021
DOI: 10.3389/fncel.2021.660561
|View full text |Cite
|
Sign up to set email alerts
|

Tonic Control of Secretory Acid Sphingomyelinase Over Ventral Hippocampal Synaptic Transmission and Neuron Excitability

Abstract: The acid sphingomyelinase (ASM) converts sphingomyelin into ceramide. Recent work has advanced the ASM/ceramide system as a major player in the pathogenesis of major depressive disorder (MDD). Indeed, ASM activity is enhanced in MDD patients and antidepressant drugs like fluoxetine act as functional inhibitors of ASM. Here, we employed the specific ASM inhibitor ARC39 to explore the acute effects of the enzyme on hippocampal synaptic transmission and cell excitability in adult mouse brain slice preparations. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This suggests that TBI’s initial insult impacts or is associated with aSMase activity, whereas chronic inflammatory effects are associated with nSMase activity. Prior studies have reported that aSMase-Cer axis regulates the pathogenesis of Major Depressive Disorder (MDD) which can occur after TBI [ 89 ]. Niziloket al, observed a similar pathology in relation to aSMase-Cer axis and accumulation of phosphorylated-tau protein in the mouse model of TBI [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that TBI’s initial insult impacts or is associated with aSMase activity, whereas chronic inflammatory effects are associated with nSMase activity. Prior studies have reported that aSMase-Cer axis regulates the pathogenesis of Major Depressive Disorder (MDD) which can occur after TBI [ 89 ]. Niziloket al, observed a similar pathology in relation to aSMase-Cer axis and accumulation of phosphorylated-tau protein in the mouse model of TBI [ 87 ].…”
Section: Discussionmentioning
confidence: 99%